ENGARUH KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP MANAJEMEN PAJAK (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016) - Dwiputra, Reyhan Adiguna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to examine and analyze the effect of institutional ownership, independent commissioners, and audit committees on tax management. Tax management is a means for carrying out taxation obligations optimally by reducing the amount of tax paid without violating the applicable rules. Tax management leads to a decrease in state’s revenues from taxation sector. This study uses secondary data with a sample of 43 manufacturing companies listed in the Indonesia Stock Exchange in the period of 2013-2016, which were determined through purposive sampling method. The data were analyzed using multiple regression analysis method. The results show that institutional ownership and independent commissioner have a significant and positive effect on tax management, while audit committee has no effect on tax managementKeywords: institutional ownership, independent commissioner, auditcommittee, tax management